Elements of Environmental Chemistry - Hites R. A. Ronald (Hoboken, John Wiley & Sons, Inc., 2012)
Providing readers with the fundamentals of environmental chemistry and a toolbox for putting them into practice. Elements of Environmental Chemistry, Second Edition is a concise, accessible, and hands-on volume designed for students and professionals working in the chemical and environmental sciences. Tutorial in style, this book fully incorporates real-world problems and extensive end-of-chapter problem sets to immerse the reader in the field. Chapters cover mass balance, chemical kinetics, carbon dioxide equilibria, pesticide structures and much more. Extensively revised, updated, and expanded, this Second Edition includes new chapters on atmospheric chemistry, climate change, and polychlorinared biphenyls and dioxins, and brominated flame retardants. in addition, new practice problems and a helpful tutorial on organic chemistry names and structures have been added to improve both the scope and accessibility of the book.